Encyclopedia of children, adolescents, and the media - Arnett, Jeffrey Jensen (Gale virtual reference library, 2007)
Presents research and facts on the media's interaction with children and adolescents. Covers the traditional and electronic media and their controversial impact on children and adolescents.